2003
DOI: 10.1094/mpmi.2003.16.10.876
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plant-Pathogenic Fungi by the Barley Cystatin Hv-CPI (Gene Icy) Is Not Associated with Its Cysteine-Proteinase Inhibitory Properties

Abstract: The recombinant barley cystatin Hv-CPI inhibited the growth of three phytopathogenic fungi (Botrytis cinerea, Colletotrichum graminicola, and Plectosphaerella cucumerina) and the saprotrophic fungus Trichoderma viride. Several mutants of barley cystatin were generated by polymerase chain reaction approaches and both their antifungal and their cysteine-proteinase inhibitory properties investigated. Point mutants R38-->G, Q63-->L, and Q63-->P diminished their capacity for inhibiting papain and cathepsin B, retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 33 publications
5
73
1
2
Order By: Relevance
“…However, A. niger was more susceptible, since it required a lesser AhCPI concentration to inhibit spore germination compared with A. parasiticus . Accordingly, it has been suggested that the cystatin inhibitory effect is determined by the fungal species (Porruan et al 2013); this hypothesis is in agreement with this study and others (Joshi et al 1998; Pernas et al 2000; Martínez et al 2003; Valdés-Rodríguez et al 2010). These results may be explained in terms of cell wall organization and composition, which are extremely variable and depend on many factors such as environmental changes, developmental stage, fungal species, etc.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…However, A. niger was more susceptible, since it required a lesser AhCPI concentration to inhibit spore germination compared with A. parasiticus . Accordingly, it has been suggested that the cystatin inhibitory effect is determined by the fungal species (Porruan et al 2013); this hypothesis is in agreement with this study and others (Joshi et al 1998; Pernas et al 2000; Martínez et al 2003; Valdés-Rodríguez et al 2010). These results may be explained in terms of cell wall organization and composition, which are extremely variable and depend on many factors such as environmental changes, developmental stage, fungal species, etc.…”
Section: Resultssupporting
confidence: 92%
“…The phytocystatin isolated from taro corms ( Colocasia esculenta ) was able to inhibit mycelial growth and cause the lysis of sclerotia in Sclerotium rofsii (Yang & Yeh 2005). The recombinant barley and chestnut cystatin inhibited the growth of Botrytis cinerea, Colletotrichum graminicola, Septoria nodorum and Plectosphaerella cucumerina ; interestingly, it did not affect Trichoderma viride (Pernas et al 2000; Martínez et al 2003). In the case of cystatin from siam tulip, the protein abolished mycelial growth of F. oxysporum, Colletotrichum capsici and Pyricularia grisea at different levels; 5 μM inhibited almost 100% of P. grisea whereas, F. oxysporum and C. capsici required almost 10 μM to reach the same level of inhibition (Porruan et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations